Longitudinal changes and determinants of parental willingness to pay for the prevention of childhood overweight and obesity - Romy Lauer; Meike Traub; Sylvia Hansen; Reinhold Kilian; Jürgen Michael Steinacker; Dorothea Kesztyüs (Health Economics Review, 2020)
Background: Willingness to Pay (WTP) is an alternative to measure quality-adjusted life years for cost-effectiveness analyses. The aim was to evaluate longitudinal changes and determinants of parental WTP for the prevention of childhood overweight and obesity. Methods: Longitudinal data from post- (T2) and follow-up (T3) measurements of a school-based health promotion program in Germany. Parental questionnaires included general WTP and the corresponding amount to reduce incidental childhood overweight and obesity by half. Longitudinal differences were examined with the McNemar test for general WTP and the Wilcoxon signed-rank test for the amount of WTP. Regression analyses were conducted to detect determinants. Results: General parental WTP significantly decreased from 48.9% to 35.8% (p < 0.001, n = 760). Logistic regression analysis (n = 561) showed that parents with a tertiary education level and a positive general WTP at T2, families with a higher monthly household income, and those with abdominally obese children were significant predictors of general WTP at T3. Median amount of WTP at T3 was exteuro20.00 (mean = exteuro27.96 ± 26.90, n = 274). Assuming a WTP of exteuro0 for those who were generally not willing to pay or did not answer, resulted in a median amount of WTP at T3 of exteuro0 (m= exteuro8.45, sd = exteuro19.58, n = 906). According to linear regression analysis WTP at T2 was the only significant predictor for the amount of WTP at T3 (p = 0.000, n = 181). Conclusions: Despite the decline of general WTP, these results are a reflection of the public awareness of the problem and the need for action. Policy makers should recognize this and initiate sustainable public preventive strategies.
Keywords: 330; Willingness to pay; Health economics; Childhood obesity; Intervention; Health promotion and prevention; Public health